The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.adolescence.2013.12.006
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of adolescent risk and protective factors for problem gambling among young adults

Abstract: There is a paucity of research examining prospective predictors of problem gambling. The current study utilised a large longitudinal data set (N = 2328) to examine a large range of adolescent risk and protective factors for problem gambling in young adulthood. These risk and protective factors covered the domains of the community, family, school, peer group and individual. Numerous predictors associated with the family, school and peer‐individual were statistically significant in analyses adjusted for gender a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
34
2
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 29 publications
(48 reference statements)
7
34
2
2
Order By: Relevance
“…Interestingly, however, alcohol use, drug use, and distress tolerance were not related to problem gambling severity in the overall sample, problem gamblers with personality disorders, or problem gamblers without personality disorders. These are unexpected findings, given consistent previous evidence of the high comorbidity between problem gambling and alcohol and substance use problems Lorains et al 2011;Scholes-Balog et al 2014;Scholes-Balog et al 2015a, b) and emerging evidence evidence that difficulty with emotion regulation is also a feature of problem gambling (Brown et al 2014;de Lisle et al 2012de Lisle et al , 2014Francis et al 2015;Lee et al 2008). Although the lack of significant findings relating to alcohol and drug use is likely due to the psychometric limitations of their measurement using single unvalidated items, the reason for the failure to identify a significant relationship between problem gambling and distress tolerance is less clear, particularly given that psychological distress was so strongly related to problem gambling severity.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Interestingly, however, alcohol use, drug use, and distress tolerance were not related to problem gambling severity in the overall sample, problem gamblers with personality disorders, or problem gamblers without personality disorders. These are unexpected findings, given consistent previous evidence of the high comorbidity between problem gambling and alcohol and substance use problems Lorains et al 2011;Scholes-Balog et al 2014;Scholes-Balog et al 2015a, b) and emerging evidence evidence that difficulty with emotion regulation is also a feature of problem gambling (Brown et al 2014;de Lisle et al 2012de Lisle et al , 2014Francis et al 2015;Lee et al 2008). Although the lack of significant findings relating to alcohol and drug use is likely due to the psychometric limitations of their measurement using single unvalidated items, the reason for the failure to identify a significant relationship between problem gambling and distress tolerance is less clear, particularly given that psychological distress was so strongly related to problem gambling severity.…”
Section: Discussionmentioning
confidence: 51%
“…Both cross-sectional and longitudinal studies have shown that individuals with BPD display significantly higher levels of substance use problems compared to individuals with other types of personality disorders (Walter et al 2009;Zanarini et al 2010). Similarly, alcohol and substance use disorders are commonly comorbid with problem gambling, in both cross-sectional and longitudinal research Lorains et al 2011;Scholes-Balog et al 2014;Scholes-Balog et al 2015a, b). A recent meta-analysis indicated that 21.2 % of treatmentseeking problem gamblers reported alcohol use disorders and 7.0 % reported substance (non-alcohol) use disorders .…”
Section: Introductionmentioning
confidence: 92%
“…Importantly, the mobile telephone‐only sample seems to include respondents characterized by characteristics deemed typically ‘hard to reach’ by conventional landline sampling approaches. They also display demographic 10, 20, 36 and psychosocial 10, 12, 14, 16, 37, 38 profiles that are associated typically with problem gambling. Indeed, the finding that the mobile‐only sample reported higher rates of problem gambling 12, 14 and endorsement of problem gambling measure items 12 suggest that the gambling field has been omitting the exact population most likely to endorse gambling problems.…”
Section: Discussionmentioning
confidence: 99%
“…La existencia de una relación parental pobre se asocia con factores que contribuyen al desarrollo de conductas adictivas. Los estudios han observado que el grupo formado por probables personas jugadoras patológicas jóvenes y el grupo de riesgo de desarrollo de la ludopatía, percibían un apoyo familiar menor (Scholes-Balog et al, 2014). Muchos jóvenes en esta situación percibían a sus progenitores y a otros familiares importantes como poco cariñosos, severos o demasiado críticos, sintiéndose emocionalmente distanciados o distantes de los miembros de la familia.…”
Section: Variables Infl Uyentes Y Factores De Riesgounclassified
“…Sin embargo, desde hace un tiempo se ha observado un incremento notable del número de jóvenes que sufren o están al borde de la ludopatía (Kuss y Griffi ths, 2012;Muñoz-Molina, 2008;Petit et al, 2015;Scholes-Balog et al, 2014;Splevins et al, 2010). En torno a otros "consumos de riesgo", como el de tabaco y alcohol, se han generado amplios consensos sobre la necesidad de alertar de los daños asociados y prohibir el acceso a los menores de edad, promoviendo así un "consumo responsable".…”
Section: Introductionunclassified